THE ROLE OF DOMESTIC AND FOREIGN INVESTMENTS IN REDUCING UNEMPLOYMENT IN ASEAN: A 1999-2023 PANEL ARDL ANALYSIS - Pratysto, Tangguh (Transpublika Publisher, 2025)
Unemployment is a challenge in economic development in ASEAN countries because its members are mostly developing countries that have market potential in Asia. Many countries in ASEAN face a mismatch in workforce skills, high levels of workers in the informal sector, and limited job opportunities for less skilled job seekers. Therefore, the government needs to understand how FDI and domestic investment affect unemployment in ASEAN in order to formulate short-term and long-term public policies to optimize investment strategies to create sustainable jobs. This study analyzes the impact of domestic investment per GDP and FDI per GDP on unemployment in ASEAN countries in the period 1999-2023. This study uses the Panel Autoregressive Distributed Lag analysis method to see the short-term and long-term effects. The results of the research show that domestic investment per GDP and unemployment have no impact in the short term but have a negative and significant effect in the long term. Then, FDI per GDP and unemployment have a positive and significant effect in the short term but have a negative and significant effect in the long term. In conclusion, foreign and domestic investment has a role in reducing unemployment in the long term and needs to be encouraged by appropriate policies.